Numerical analysis of heavy cob walls’ hygrothermal behavior - Aguerata Kabore; Mathieu Bendouma; Claudiane Ouellet-Plamondon (Energy and Buildings, 2025)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Plastic response of fearful prey to the spatiotemporal dynamics of predator distribution - Mathieu Basille; Daniel Fortin; Christian Dussault; Guillaume Bastille-Rousseau; Jean-Pierre Ouellet; Réhaume Courtois (Ecology, 2015)
Ecological theory predicts that the intensity of antipredator responses is dependent upon the spatiotemporal context of predation risk (the risk allocation hypothesis). However, most studies to date have been conducted over small spatial extents, and did not fully take into account gradual responses to predator proximity. We simultaneously collected spatially explicit data on predator and prey to investigate acute responses of a threatened forest ungulate, the boreal caribou ( Rangifer tarandus ), to the spatiotemporal dynamics of wolf ( Canis lupus ) distribution during spring. Movement analysis of GPS‐collared individuals from both species revealed high plasticity in habitat‐selection decisions of caribou. Female caribou avoided open areas and deciduous forests and moved relatively fast and toward foraging areas when wolves were closer than 2.5 km. Caribou also avoided food‐rich areas only when wolves were within 1 km. Our results bridge the gap between long‐term perceived risk and immediate flight responses by revealing dynamic antipredator tactics in response to predator proximity.